(untitled) (Development Service Industry Management, 2024)
The article focuses on issues of formation and implementation of socially responsible policies by business entities. Emphasis is placed on the specifics, as well as the need for planning and implementation of socially responsible activities by entities in the field of consumer services. The purpose of the study is to further develop the theoretical and methodological principles of social responsibility management of entities in the field of consumer services. The changes in the directions of socially responsible policy implementation by subjects of the sphere of consumer services of Ukraine in the conditions of war are shown. It was concluded that in order to solve the problems and remove most of the obstacles to the activation of the social responsibility of the entities in the field of consumer services, it is appropriate to develop and implement measures in the following directions (operational tasks): (1) improvement of the system of protection of workers’ rights and ensuring compliance with labor legislation (legalization of employment and wages; increasing the amount of capital investments in the development of intellectual capital; strengthening of social protection and development of social infrastructure; increasing the level of wages and the adequacy of the amount of the employee’s contribution to the economic results of the entity in the field of consumer services); (2) strengthening the social responsibility of business to society (increasing the number of new jobs; introducing quality management systems for compliance with industry and collective agreements at entities in the field of consumer services); (3) improvement of relations between subjects of the sphere of consumer services and the consumer sector (improvement of the system of protection of consumer rights; improvement of quality characteristics and ensuring the safety of services; strengthening of responsibility for price policy); (4) increasing the role of representatives of subjects of the field of consumer services in the protection of the environment; (5) ensuring a high level of social responsibility of entities in the field of consumer services to counterparties and competitors.